1985
DOI: 10.1111/j.1365-2621.1985.tb13797.x
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth Flour Blends and Fractions for Baking Applications

Abstract: Selected Amaranthus eruentus ecotypes from different places of origin were used to prepare baking products. Amylograph, alveograph and farinograph data of mixtures of white wheat flour with whole amaranth grain flour from raw, toasted and popped amaranth seeds, as well as with higher protein fractions obtained by air classification, presented clear differences with respect to wheat flour. Six selected amaranth lines displayed different behaviors according to their origin and the seeds' previous treatment. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…186 Flour blends with amaranthus have been used successfully to prepare enriched cookies and bolillos. 138 Several investigators have demonstrated that sorghum and millet flours can be blended with wheat flour to produce acceptable cookies and biscuits. "M.CT.130.187-1M De Ruiter 192 prepared hard or soft biscuits from composite flour and prepared cookies with entirely nonwheat flour containing 67% cassava starch and 33% defatted soy flour or 100% sorghum or millet flour by rotary molding or depositing.…”
Section: Nonwheat Cerealsmentioning
confidence: 99%
“…186 Flour blends with amaranthus have been used successfully to prepare enriched cookies and bolillos. 138 Several investigators have demonstrated that sorghum and millet flours can be blended with wheat flour to produce acceptable cookies and biscuits. "M.CT.130.187-1M De Ruiter 192 prepared hard or soft biscuits from composite flour and prepared cookies with entirely nonwheat flour containing 67% cassava starch and 33% defatted soy flour or 100% sorghum or millet flour by rotary molding or depositing.…”
Section: Nonwheat Cerealsmentioning
confidence: 99%
“…It can also be made into flakes, porridge and flour; typical uses of amaranth have been summarized by Breene (1991). As a whole grain, amaranth is being increasingly used in breads and cookies (Sanchez-Marroquin, Domingo, Maya, & Saldana, 1985) as well as pasta and breakfast cereals (Lehmann, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…2 '" 7) There are many reports that show their superior nutritional value and promise for feeding the world's hungry. [8][9][10][11][12][13][14][15] The major protein in amaranth grain has been shown to be albumin and globulin fractions. 16 -21) We have previously purified 440-kD globulin from Amaranthus hypochondriacus seeds 1 7) and investigated the preliminary functional properties of the globulin.…”
mentioning
confidence: 99%